213k views
4 votes
Consider the transformation T: x = \frac{56}{65}u - \frac{33}{65}v, \ \ y = \frac{33}{65}u + \frac{56}{65}v

A. Computer the Jacobian:
\frac{\partial(x, y)}{\partial(u, v)} =
B. The transformation is linear, which implies that ittransforms lines into lines. Thus, it transforms the squareS:-65 \leq u \leq 65, -65 \leq v \leq 65 into a square T(S) with vertices:
T(65, 65) =
T(-65, 65) =
T(-65, -65) =
T(65, -65) =
C. Use the transformation T to evaluate the integral\int \!\! \int_{T(S)} \ x^2 + y^2 \ {dA}

User Tsung Wu
by
5.8k points

1 Answer

3 votes

Answer:

Explanation:


T: x = (56)/(65)u - (33)/(65)v, \ \ y = (33)/(65)u + (56)/(65)v

A)


(d(x,y))/(d(u,v)) =\left|\begin{array}{ccc}x_u&x_v\\y_u&y_v\end{array}\right|


=((56)/(65) )^2+((33)/(65) )^2\\\\=((56)^2+(33)^2)/((65)^2) \\\\=(4225)/(4225) \\\\=1

B )


S:-65 \leq u \leq 65, -65 \leq v \leq 65


T(65,65)=(x=(56)/(65) (65)-(33)/(65) (65),\ \ y =(33)/(65) (65)+(56)/(65) (65)\\\\=(23,89)


T(-65,65)=(-56-33,\ \ -33+56)\\\\=(-89,23)


T(-65,-65) = (-56+33,-33-56)\\\\=(-23,-89)


T(65,-65)=(56+33, 33-56)\\\\=(89,-23)

C)


\int \!\! \int_(T(S)) \ x^2 + y^2 \ {dA}


=\int\limits^(65)_(v=-65) \int\limits^(65)_(u=-65)(x^2+y^2)((d(x,y))/(d(u,v)) du\ \ dv

Now


x^2+y^2=((56)/(65) u-(33)/(65) v)^2+((33)/(65) u+(56)/(65) v)^2


[((56)/(65) )^2+((33)/(65)) ^2]u^2+[((33)/(65) )^2+((56)/(65)) ^2]v^2


=((65)^2)/((65)^2) u^2+((65)^2)/((65)^2) v^2=u^2+v^2


\int \!\! \int_(T(S)) \ x^2 + y^2 \ {dA}


=\int\limits^(65)_(v=-65) \int\limits^(65)_(u=-65)(u^2+v^2) du\ \ dv


=\int\limits^(65)_(-65)\int\limits^(65)_(-65)u^2du \ \ dv+\int\limits^(65)_(-65)\int\limits^(65)_(-65)v^2du \ \ dv

By symmetry of the region


=4\int\limits^(65)_0 \int\limits^(65)_0u^2 du \ \ dv + u\int\limits^(65)_0 \int\limits^(65)_0v^2 du \ \ dv


= 4((u^3)/(3) )^(65)_(0)(v)_0^(65)+((v^3)/(3) )^(65)_(0)(u)_0^(65)\\\\=4[((65)^4)/(3) +((65)^4)/(3) ]


=(8)/(3) (65)^4

User Ghchoi
by
4.9k points